DEVOSI MARIAL LEGIO MARIA DAN PEMBAKTIAN DIRI MENURUT MONTFORT - Pasi, Gregorius; Marselina Murni; Angelina Ina Bora (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2024)
This study is intended to answer the following status quaestionis: Why did Frank Duff (the founder of the Legion of Mary) reques legionaries to practice marian devotion taught by Montfort, namely consecration to Jesus through Mary? The answer is supposed to motivate the legionaries to live the Montfort consecration. In order to answer the question, we use the critical analysis method and critical dialectic method on the related data. We find that the aim of the Legion of Mary and the Montfort consecration is the same. Hence, Montfort consecration is a type of marian devotion that can perfectly bering legionaries to the goal of the Legion of Mary, namely the glory of God through the holiness of its members. Keywords: consecration, holines, Legion of Mary, marian devotion, Mary’s maternal role